Pemilihan Jenis Loji yang Sesuai Digunakan di Malaysia - Shahrun, Akmal Syahin; Abd Rahim, Mohd Hilmi Izwan (Research in Management of Technology and Business, 2023)
The rapid development and growth of new cities, then the need in the management of the sewerage service system is increasingly pressing. In relation to that, a solution needs to be found in providing a balance between development and environmental sustainability so that all sewage waste that is released can be treated. So, this study will look at the potential of choosing the type of plant that is suitable for use in Malaysia. However, a study needs to be done and three objectives have been determined which are to study the factors of plant type selection in Malaysia, study the effects of the failure of the management system of wastewater treatment plants in Malaysia and suggest improvements in the existing management system. In achieving the objective of the study, an analysis method is used which is the qualitative method. This qualitative method involves a total of six respondents who will be interviewed who are staff members of the Indah Water Konsortium. This study brings importance in treating sewage waste by ensuring a systematic sewage treatment plant management system can be implemented to improve processing quality. In relation to that, the researcher would like to see the importance in selecting the appropriate type of sewage treatment plant in Malaysia that can provide benefits and benefits in securing public health, the environment and the country’s water resources. In conclusion, the party responsible for managing the sewage treatment plant should improve the quality of work in operating the sewage plant so as not to cause environmental pollution and affect users.